PENGAWASAN PENGGUNAAN KENDARAAN BERMOTOR OLEH SATUAN LALU LINTAS POLISI RESOR KOTA PEKANBARU (STUDI KASUS ANAK DI BAWAH UMUR) - Stella Graldina Puspala; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Satlantas Polresta Pekanbaru has the main tasks and functions to maintain security, comfort, fluency and law and order of traffic in Pekanbaru City. One of it’s function is to take controlling the using of vehicle by chidren under the age. Currently, the phenomenon of the use of vehicle by children under the age is still a lot happening, even since they are in Junior High School. This research aims to know how controlling the using of vehicle children under the age by Satlantas Polresta Pekanbaru and the inhibition factors. This research used the theory of controlling by the time of it’s implementation by Erni and Saefulah, that is preventive controlling, controlling of the process, and refresif controlling. The writer used qualitative research method with snowball sampling as sampling thecnique. This research result indicates that the controlling the using of vehicle by Satlantas Polresta Pekanbaru (case study of minors) the preventive controlling, controlling by the process, and refresif controlling has a lot of inhibition factors. The inhibition factors consist of: internal factors that is, lack of human resources, double job, budget is not enough, disposation of employee, narrow area of work, inadequate facilities and infrastructure, and external factors that it less participation and rules obeydian of society.Keywords: Controlling, Satlantas, Minors, Pekanbaru.